The affective life of law - Reichman, Ravit Pe'er-Lamo (Stanford Univ. Press, 2009)
Woolf and the lesson of torts – The strange character of law – Property and carrying on – Committed to memory : Rebecca West's Nuremberg – From witness to neighbor : Arendt's Eichmann – Epilogue : justice without proportion
Includes bibliographical references and index
Keywords: Law and literature; Law in literature; Trials in literature